2010
DOI: 10.1128/aem.00120-10
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Monitoring Programmed Cell Death and Differentiation in Submerged Streptomyces Cultures

Abstract: Vital stains were used in combination with fluorimetry for the elaboration of a new method to quantify Streptomyces programmed cell death, one of the key events in Streptomyces differentiation. The experimental approach described opens the possibility of designing online protocols for automatic monitoring of industrial fermentations.Streptomyces is an extremely important bacterium for industry, since approximately two-thirds of all antibiotics are synthesized by members of this genus (4). Furthermore, streptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…A simple methodology based on fluorometric measures of cultures stained with SYTO9 and propidium iodide was designed to quantify PCD in liquid cultures [ 69 ]. This method allows the efficiency of antibiotic production to be predicted based on the level of PCD [ 69 ].…”
Section: Screening For New Secondary Metabolites From Stmentioning
confidence: 99%
“…A simple methodology based on fluorometric measures of cultures stained with SYTO9 and propidium iodide was designed to quantify PCD in liquid cultures [ 69 ]. This method allows the efficiency of antibiotic production to be predicted based on the level of PCD [ 69 ].…”
Section: Screening For New Secondary Metabolites From Stmentioning
confidence: 99%
“…18,19 The traditionally denominated substrate mycelium corresponds to MII lacking hydrophobic layers, and the aerial mycelium to MII coated with these hydrophobic layers (Figure 1). 15 The only mycelial phases present in liquid cultures were MI and MII without hydrophobic layers 8,9 (Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…The lack of a reliable developmental model in streptomycetes liquid cultures has hindered the precise identification of reliable phenotypes for use in the analysis and optimization of industrial fermentations. It has been demonstrated that antibiotics are produced by the substrate mycelium at the end of the proliferation phase, i.e., second mycelium morphology (after PCD process) [27,30,37]. However, despite the fact that there is a distinctive mycelium producing antibiotics (MII) [27, 30] (hence there is not secondary metabolite production until the differentiation of MII), antibiotic production has additional regulations, and each Streptomyces strain does not display its entire potential secondary metabolism at a specific developmental condition.…”
Section: Correlation Between Streptomyces Life Cycle and Antibiotic Pmentioning
confidence: 99%
“…The N-acetylglucosamine resulting from peptidoglycan dismantling accelerates the development and antibiotic production [108,109] and might be one of the signals released during PCD. A simple methodology based on fluorimetric measures was designed to quantify PCD in liquid cultures [37], allowing prediction of the efficiency of antibiotic production based on the level of PCD.…”
Section: Programmed Cell Death and MII Differentiationmentioning
confidence: 99%